Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Pengguna Jalan Tol Dalam Kota Tahun 2025 - Utomo, Rudi; sari, Imelda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Jasamarga Metropolitan Tollroad is a regional division of PT Jasa Marga (Persero) Tbk that operates in the toll road service sector in Indonesia. This study aims to analyze the effect of service quality and corporate image on toll road user satisfaction at Jasamarga Metropolitan Tollroad. This research employs a quantitative approach by collecting data through an online questionnaire distributed to 100 respondents selected using a purposive sampling technique. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects among variables. The results indicate that service quality has a significant effect on user satisfaction, as shown by a t-value of 3.848 which is higher than the t-table value of 1.985 and a significance level of 0.000 < 0.05. Corporate image also has a significant effect on user satisfaction, indicated by a t-value of 4.572 > 1.985 with a significance level of 0.000 < 0.05. Simultaneously, service quality and corporate image significantly influence user satisfaction with an F-value of 83.906 > 3.090 and a significance level of 0.000 < 0.05. These findings indicate that improving service quality and strengthening corporate image are important factors in increasing toll road user satisfaction. This study contributes empirically to the marketing management literature, particularly in understanding the determinants of user satisfaction in toll road services.